Prenatal and childhood chlordecone exposure, cognitive abilities and problem behaviors in 7-year-old children: the TIMOUN mother-child cohort in Guadeloupe - Youssef Oulhote; Florence Rouget; Léah Michineau; Christine Monfort; Mireille Desrochers-Couture; Jean-Pierre Thomé; Philippe Kadhel; Luc Multigner; Sylvaine Cordier; Gina Muckle (BMC, 2023)
Abstract Background Chlordecone is a highly persistent organochlorine insecticide that was intensively used in banana fields in the French West Indies, resulting in a widespread contamination. Neurotoxicity of acute exposures in adults is well recognized, and empirical data suggests that prenatal exposure affects visual and fine motor developments during infancy and childhood, with greater susceptibility in boys. Objective To assess the associations between pre- and postnatal exposures to chlordecone and cognitive and behavioral functions in school-aged children from Guadeloupe. Methods We examined 576 children from the TIMOUN mother-child cohort in Guadeloupe at 7 years of age. Concentrations of chlordecone and other environmental contaminants were measured in cord- and children's blood at age 7 years. Cognitive abilities of children were assessed with the Wechsler Intelligence Scale for Children-IV (WISC-IV), and externalizing and internalizing problem behaviors documented with the Strengths and Difficulties Questionnaire (SDQ) completed by the child's mother. We estimated covariate-adjusted associations between cord- and 7-years chlordecone concentrations and child outcomes using structural equations modeling, and tested effect modification by sex. Results Geometric means of blood chlordecone concentrations were 0.13 µg/L in cord blood and 0.06 µg/L in children's blood at age 7 years. A twofold increase in cord blood concentrations was associated with 0.05 standard deviation (SD) (95% Confidence Interval [CI]: 0.0, 0.10) higher internalizing problem scores, whereas 7-years chlordecone concentrations were associated with lower Full-Scale IQ scores (FSIQ) and greater externalized behavioral problem scores. A twofold increase in 7-year chlordecone concentrations was associated with a decrease of 0.67 point (95% CI: -1.13, -0.22) on FSIQ and an increase of 0.04 SD (95% CI: 0.0, 0.07) on externalizing problems. These associations with Cognitive abilities were driven by decreases in perceptive reasoning, working memory and verbal comprehension. Associations between 7-year exposure and perceptive reasoning, working memory, and the FSIQ were stronger in boys, whereas cord blood and child blood associations with internalizing problems were stronger in girls. Conclusions These results suggests that cognitive abilities and externalizing behavior problems at school age are impaired by childhood, but not in utero, exposure to chlordecone, and that prenatal exposure is related to greater internalizing behavioral problems.